An analysis of pseudomonas aeruginosa bacteraemia over a 2-year period - Perovic, Olga (My University, 2004)
In this dissertation the clinical manifestations, outcome and prognostic factors associated with Pseudomonas aeruginosa bacteraemia were assessed prospectively, resistance to anti-pseudomonal drug described and quantified, and phenotypic methods applied clinical isolates for epidemiological purposes.
Dissertation submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Master of Science in Medicine